(untitled) (Damascus University Journal for engineering sciences, 2022)
The seaports in Syria suffer from an increase in the number of containers and a continuous decline in free spaces, which calls for enabling the performance of these ports to reach the maximum capacity without the need for expansion and development on the elements and components of the infrastructure, but by focusing on solutions associated with the integration of infrastructures for transportation patterns and activation of dry ports. This paper focuses on studying the time of container transport in the logistical transport network between sea and dry ports, as the process of organizing container transport in the optimal pattern will positively affect the improvement of the transport process. In this research, we put a mathematical model describing the time required to transport containers between Lattakia port and a number of dry ports. after obtaining the data on transport operations. In the end, the modeling process for that data was carried out, and by comparison between the road and rail transport networks, the results showed the efficiency of trains in the containers transport process in terms of productivity and the time required for the transport process.